2010
DOI: 10.1111/j.1447-0756.2010.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual versus vaginal misoprostol for the management of missed abortion

Abstract: Sublingual misoprostol for the medical management of missed abortion is more effective and more acceptable than the vaginal route. However, it showed more adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
5
15
0
1
Order By: Relevance
“…Sublingual route is more effective in successful evacuation than the vaginal route, but the main point of weakness here is delayed action. Another study showed a similar result to that of Tanha FD et al who showed that the effectiveness was higher in the sublingual group and the difference statistically significant (sublingual 84.5 %, vaginal 46.4 %, P = 0.000, RR = 0.54, 95 % CI = 0.442-0.681) [15] and the study by Shah et al found that there was no significant difference in the complete evacuation rates between the sublingual misoprostol and the vaginal misoprostol groups (52 vs. 48 %, P = 0.571) [10]. The explanation for this difference was that the last study had a fewer numbers of cases and it had extended the gestational age of cases up to 20 weeks.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Sublingual route is more effective in successful evacuation than the vaginal route, but the main point of weakness here is delayed action. Another study showed a similar result to that of Tanha FD et al who showed that the effectiveness was higher in the sublingual group and the difference statistically significant (sublingual 84.5 %, vaginal 46.4 %, P = 0.000, RR = 0.54, 95 % CI = 0.442-0.681) [15] and the study by Shah et al found that there was no significant difference in the complete evacuation rates between the sublingual misoprostol and the vaginal misoprostol groups (52 vs. 48 %, P = 0.571) [10]. The explanation for this difference was that the last study had a fewer numbers of cases and it had extended the gestational age of cases up to 20 weeks.…”
Section: Discussionsupporting
confidence: 73%
“…Shah et al found that the mean times to expulsion were also similar in respect of both groups (13.07 ± 6.95 h for sublingual versus 13.29 ± 5.63 h for vaginal group) [10], while Tanha et al found that the mean time to expulsion was shorter (9.68 h, SD = 5.51, 95 % CI = 8.61-10.57) in the sublingual group than that in the vaginal group (16.64 h, SD = 14.01, 95 % CI = 13.8-19.48), P = 0.000 [15]. The reason for the contradiction between the previous two studies and this study, in relation to rapid action of vaginal route, is that those studies have used higher doses of misoprostol than the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The security of waiting at home needs further researched, especially for the incidence of excessive bleeding. For women needed emergency operation, cervical ripening was prepared due to the medical treatment and it is convenient to perform dilatation and curettage 24, 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A higher intravaginal dosage (800 vs 600 μg) was found to result in increased rates of complete abortion within 24 h and was not associated with a higher rate of side‐effects . The sublingual route was found to be more effective than the oral or intravaginal routes but at the same time was associated with a higher rate of side‐effects . Sonographic parameters, such as gestational sac size, gestational age, and fetal size, have all been additionally suggested as factors influencing success rates …”
Section: Introductionmentioning
confidence: 99%